Investigation of the Phase Change during Solid Phase Synthesis of Bi1.7Pb0.3Sr2Can-1cunoy Bismuth-Based Cuprates - Gayrat ogli, Turayev Ozodjon (American Journal of Biodiversity, 2024)
There are different preparation technologies of any kind of cuprates. This article talks about the technology of obtaining bismuth-based cuprates and the aspects that need to be paid attention to in this process. The advantages and disadvantages of obtaining BSCCO cuprate by solid state reaction method are presented. At the same time, it was mentioned why cuprates of this type of superconducting phase appear in several phases instead of one, and these reasons are explained in a simple way. The steps for obtaining BSCCO cuprate by the solid state reaction method are listed in sequence. The constituents of the BSCCO composite material, the role of each element in the mixture was studied under an optical microscope. The formation of the overall structure near the melting temperature was analyzed by microscopic images.